2021
DOI: 10.3390/jfmk6030058
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthritis and Strength Training: A 4-Year Report

Abstract: Peripheral spondyloarthritis (SpA) has predominant peripheral (arthritis, enthesitis, or dactylitis) involvement. The severity of the symptoms can have a significant impact on the quality of life. There is no therapeutic gold standard, and physical exercise, with the opposition of resistance, remains controversial. Herein, we report the case of a woman who, at the age of 50, comes to our center with evident motor difficulties. She was previously diagnosed with SpA and was in therapy with a biological drug (ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This might guarantee an adequate progression of the training schemes and their execution. We have, in fact, shown in two case reports how two women aged 52 and 72 with osteoarticular pathologies (spondyloarthritis and osteoarthritis, respectively) have obtained significant improvements in powerlifting performance (+100 kg in deadlift) and in QOL (Cannataro et al, 2021b ; Malorgio et al, 2021 ). From the basic strength conditioning to specific results, they spend 2 and 5 years, respectively.…”
Section: Strength Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…This might guarantee an adequate progression of the training schemes and their execution. We have, in fact, shown in two case reports how two women aged 52 and 72 with osteoarticular pathologies (spondyloarthritis and osteoarthritis, respectively) have obtained significant improvements in powerlifting performance (+100 kg in deadlift) and in QOL (Cannataro et al, 2021b ; Malorgio et al, 2021 ). From the basic strength conditioning to specific results, they spend 2 and 5 years, respectively.…”
Section: Strength Trainingmentioning
confidence: 99%
“…Various types of resistance training have been proposed as useful approaches for improving body composition, muscle strength, power, and physical function in older adults (Baena-Marín et al, 2022 ). Among these, suspension-based resistance training (S-RT) involves attaching body segments to suspended hanging straps, creating an unstable environment, and performing multi-planar and multi-joint exercises while fighting gravity (Byrne et al, 2014 ; Mok et al, 2015 ; Cugliari and Boccia, 2017 ; Consitt et al, 2019 ; Cannataro et al, 2021b ). Research on the acute effects of S-RT has shown similar results compared to traditional weight resistance training conducted in a stable environment (Sun et al, 2018 ; Jiménez-García et al, 2019 ).…”
Section: Non-traditional Resistance Trainingmentioning
confidence: 99%
“…Significant improvements in muscle strength and size have been reported in training programs that include 1–3 sets per exercise [ 83 ] with an adjustment of the numbers of repetitions that considers the maximum number that can be performed with a given intensity (max effort) [ 84 ]. Even in delicate conditions such as osteoarthritis or spondylarthritis, strength training can give excellent results [ 85 , 86 ]. Lastly, in order to continually reach improvements in mass, strength, and functional capacity, it is key to consistently incorporate progression and variation into the program.…”
Section: Counteracting Strategiesmentioning
confidence: 99%